Comparison between two therapeutic approaches to post-operative pain in urological surgery Psychological and pharmacological aspects - Sergio Manfré; Silvano G. Cella; Gianni L. Bert; Antonio M. Bacchioni; Paula Pettman (Publiediting, 2005)
The post-operative analgesic therapy represents a target of quality and saving for a Hospital because it ensures a positive outcome for surgery-treated patients. From this point of view, it is important to use validated protocols in each specific clinical context and to pay attention to all the factors involved in the genesis of pain...In this study the analgesic benefit offered by different protocols of treatment of post-operative pain in 88 patients who underwent an operation of transurethral prostatectomy (TURP) has been evaluated. In addition to verifying the efficacy of different pharmacological therapies, we wanted to estimate the impact of providing the patients with detailed information before surgery on the following response to the analgesic therapy. Our present results demonstrate the validity of a therapeutic protocol based on the use of an opiate administered by continuous intravenous infusion and point out the importance of a multidisciplinary approach to the patient with post-operative pain.